Phenotype characterization of interspecific hybrid abalone Haliotis asinina and Haliotis squamata seed - Dinar Tri Soelistyowati; Aldilla Kusumawardhani; Muhammad Zairin Junior (Jurnal Akuakultur Indonesia)
ABSTRACT